Interspecific potato hybrids as donors of durable resistance to pathogens - E. V. Rogozina; E. E. Khavkin (Вавиловский журнал генетики и селекции)
Interspecific hybridization is the primary method of potato breeding for resistance to pathogens. By introgressing genetic material from various species of the genus Solanum L. and selecting the best combinations, it is possible to merge, in a single genotype, both high productivity and resistance to diseases and pests. Among the most impressing outcomes of potato breeding, we find varieties resistant to late blight, potato virus Y and nematodes. In the pedigrees of many recent varieties (breeding lines) that are resistant to pathogens of different nature (fungi, oomycetes, bacteria or viruses), we find genetic material of Solanum andigenum, S. demissum, S. stoloniferum, S. acaule, S. vernei and other wild and cultivated potato species. The breeding value of tuber-bearing Solanum species depends on their compatibility with the cultivated potato and the mechanism of target trait inheritance. To overcome incompatibility in crosses, breeders employ ploidy manipulation in the parental forms, bridge crosses, the mediator method and various in vitro technologies. Potato genotypic variation is significantly expanded by interspecific hybridization of wild and cultivated potato relatives. The main components of breeding technology based on interspecific potato hybrids are the identification of promising initial genotypes, the control over the introgression of the target traits through the crosses, the selection of hybrid clones prospective for practical breeding and the assessment of their donor properties. All of these processes are greatly accelerated and promoted by the methods of marker-assisted selection. Advanced lines and clones developed by interspecific hybridization manifest a high diversity of genotypes and particular genes and are unique donors for breeding new varieties maintaining high and durable resistance to diseases and pests.